The dark triad and organizational citizenship behavior in health care: The moderating role of positive emotions. Issue 5 (6th May 2020) - AL‐Abrrow, Hadi; Thajil, Krar Muhsin; Abdullah, Hasan Oudah; Abbas, Sammar
Abstract : The dark triad refers to a set of personality traits characteristic of narcissism, Machiavellianism, and psychopathy. Organizational citizenship behavior (OCB) describes voluntary, cooperative actions that contribute to organizational effectiveness. A study focused on the health‐care sector in Iraq investigates the therapeutic role that positive emotions might play in offsetting the negative effects of the dark triad on OCB. Data from 414 employees in four public hospitals show that the dark triad has a significant negative impact on OCB, but that positive emotions can play a role in reversing this. This finding leads to several implications for both managers and researchers. In particular, it highlights the importance of addressing the interaction between positive and negative emotions, as well as the positive organizational outcomes that potentially could result from dark triad traits.